2014
DOI: 10.1016/j.apenergy.2014.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Use of the microalga Monoraphidium sp. grown in wastewater as a feedstock for biodiesel: Cultivation and fuel characteristics

Abstract: The use of microalgae as feedstocks for biodiesel is potentially limited by climatic conditions with low light and temperature levels. Monoraphidium sp. Dek19 was identified by 18S rRNA gene sequencing. This is a species indigenous to the upper Midwestern USA which grows to high densities in wastewater with bioremediation resulting in a reduction of nitrate and phosphate levels. Mesocosm pool cultures (171L) were used to characterize growth of this species in larger volumes than typical of previous lab-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 36 publications
1
16
1
3
Order By: Relevance
“…Some of the main species of algae used in large-scale commercial production are restricted to geographic locations with warm climate and would be unable to grow at acceptable rates during the hot or cold season of certain geographical region [84]. One solution to this problem is to identify indigenous algae that are adapted to the local environment [84]. In addition, native microalgal species also performed better than most other species in commercial scale cultivation with native environment [85].…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the main species of algae used in large-scale commercial production are restricted to geographic locations with warm climate and would be unable to grow at acceptable rates during the hot or cold season of certain geographical region [84]. One solution to this problem is to identify indigenous algae that are adapted to the local environment [84]. In addition, native microalgal species also performed better than most other species in commercial scale cultivation with native environment [85].…”
Section: Speciesmentioning
confidence: 99%
“…Mixed cultures of algae can sustain themselves in complex environments, and diverse microalgal communities are considered to be more stable and have a lower invasion risk than monocultures [83]. Some of the main species of algae used in large-scale commercial production are restricted to geographic locations with warm climate and would be unable to grow at acceptable rates during the hot or cold season of certain geographical region [84]. One solution to this problem is to identify indigenous algae that are adapted to the local environment [84].…”
Section: Speciesmentioning
confidence: 99%
“…From the point of view of environmental pollution, algae can be a good resource for biodiesel production. It has been reported that application of air supplemented with carbon dioxide at the time of algae culture increases the oil content of the algae (Holbrook et al 2014;Dassey et al 2014) and biofuels from algae fix 0.6% CO 2 (Ponnusamy et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other species used are for example Monoraphidium sp., Chlorella ellipsoidea, Chlorella vulgaris, Neochloris oleoabundans or Desmodesmus sp. All these species are able to effectively remove nutrients from wastewater (Wang et al 2011;Arbib et al 2014;Holbrook et al 2014;Fang et al 2015).…”
Section: Laboratory-scale Studies Using Suspension Culturesmentioning
confidence: 99%